Faktor yang Mempengaruhi Keputusan Pembelian Gen Z pada TikTok Shop di Sukoharjo - Julia Nurul Putri Sandy; Ari Susanti (Riset Manajemen dan Akuntansi, 2025)
The background of the research is the phenomenon of the use of TikTok Shop as a social e-commerce platform combining entertainment elements and online transaction activities. This analysis applies a quantitative approach to a population of 100 Generation Z in Sukoharjo obtained using purposive sampling techniques. Data analysis uses multiple linear regression assisted by SPSS Version 26. This study found that Live Streaming and Online Customer Reviews have a positive and significant effect on purchasing decisions. The more interactive Live Streaming activities and the more positive customer reviews, this causes Generation Z's purchasing decisions on TikTok Shop to increase. Both variables can be responsible for 43.7% of the variation in purchasing decisions, according to the results of the Coefficient of Determination (R2) value of 0.437. This study confirms that direct interaction, information credibility, and trust formed through Live Streaming and Online Customer Reviews have a significant influence on Generation Z's purchasing decisions on TikTok Shop.